To exploit and dispossess: The twofold logic of platform capitalism. (1st January 2021) - Fagioli, Andrea
Abstract : This paper addresses the relation between capital and digital labour in the context of so-called platform capitalism. Based on the taxonomy proposed by A. Casilli - on-demand labour, crowdwork or microwork, and social media labour - I argue that the concept of exploitation is not sufficient to fully account for the logic of platform capitalism, as it only makes up one of its dimensions. The other central dimension is that which targets data capture, which I call, using Harvey's term, 'dispossession'. Far from proposing a fixed delimitation of the concept of labour, I argue that the two dimensions operate together and, in many cases, it is difficult to isolate them, but they do demand the invention of different political strategies.